INFLUENCE OF WOOD STACKING LOCATION ON FOREST TRANSPORT COSTS - Fernandes, Danilo Lopes; Matos, Lisandra Maria Alves; Magalhães, Emanuelly Canabrava; Cabacinha, Christian Dias; de Assis, Adriana Leandra; Araújo Júnior, Carlos Alberto (Floresta, 2019)
Given the importance of forest transportation planning due to its high contribution in wood final cost, the distance between forest plantation stands and the wood final destination should be optimized in order to reduce process cost. The relation between distance and transportation cost is known, yet, it is still necessary to evaluate how much the location of the wood piles inside the stand interferes with its final cost. Thus, we try to evaluate the influence of the wood stacking location on forest transportation costs. The vectorization of the general map of a property located in Minas Gerais state was performed through the QGIS software, by representing the planting areas by polygons, internal and external access roads by lines, and the possible wood-stacking location to be transported by points. In each stand, four wood-stacking sites were considered, each on one side of the stand. Considering this, optimal route simulations were performed based on the criterion of the shortest distance between each pile of wood and a carbonization plant. The results showed a 32% reduction in the final cost of transportation when the wood is stacked in places closer to the carbonization plant. Therefore, the results evidence that the choice of the ideal stacking point, in the aspect of closer proximity to the destination of the wood transportation, can generate savings in this process.